Studies Of The Effect Of Post Deposition Annealing To The Ceo2 Thin Film On P-Type Silicon And N-Type Silicon Carbide Substrates - Chuah, Soo Kiet (2011)
Cerium Oxide (CeO2) thin film has been deposited on silicon (Si) and silicon carbide (SiC) substrates using a radio frequency magnetron sputtering technique. The effect of post deposition annealing at different temperatures (400, 600, 800 and 1000oC) in argon (Ar) ambient for 30 minutes has been investigated on p-type Si and n-type SiC substrates. The thickness of the CeO2 thin films on Si and SiC substrates are in the range of 30 to 40 nm. Field emission scanning electron microscopy and atomic force microscopy show that both CeO2 thin films on Si and SiC substrates are free of physical defects and the root mean square surface roughness are decreasing as the annealing temperature increases.